Research of microstructure and microbiological indicators of pasta products from non-traditional raw materials - A. A. Ospanov; A. K. Timurbekova; D. Nurdan; T. Sh. Askarova; B. D. Adilkhan (Алматы технологиялық университетінің хабаршысы, 2021)
Modern trends in the development of pasta production are based on the use of starch-containing raw materials for the production of medicinal and preventive pasta products. In this connection, an important observation is the state of protein and starch in pasta flour, which can be achieved by electron microscopy of the microstructure of macaroni products. Therefore, the study of microstructures and microbiological indicators of pasta from non-traditional raw materials will be relevant. The practical value of the research is characterized by improved consumer properties of pasta made from non-traditional raw materials. The novelty of the research is the development of scientific and technological bases for the production of pasta from non-traditional polycereal raw materials. The results obtained: the analysis of the obtained electronic micro-drawings showed that the microstructure of pasta from non-traditional raw materials corresponds to the standards in comparison with the control sample. The following types of mycotoxins were found in pasta from non-traditional raw materials in permitted quantities: aflatoxin B1, aflatoxin M1, zearalenone, deoxynivalenol, ochratoxin A, fumonisin, patulin, T-2. For example, the amount of zearalenone (mg/kg): in pasta according to recipe No. 1 – 0.0637, according to recipe No. 2 – 0.0251 and according to recipe No. 3 – 0.0758; in flour raw materials – according to recipe No. 1 – 0.1485, according to recipe No. 2 – 0.0261 and according to recipe No. 3 – 0.2.